Computer-Animated Videos in Education: A Comprehensive Review and Teacher Experiences from Animation Creation - Alexandros Kleftodimos (Digital, 2024)
Animated videos have been used in education for many years, and their efficacy in enhancing student motivation, engagement, and performance has been evaluated and reported in many studies. The aim of this study is twofold. First, after examining seventy-seven research articles, this study will attempt to provide an updated comprehensive literature review on the topic for the last decade. The articles were obtained from Google Scholar and Scopus following a certain methodology (search keywords, inclusion and exclusion criteria). The articles were examined for aspects such as the educational fields in which animated videos have been utilized over the last ten years, the researchers’ countries, the types of animated videos, the software tools used to create the educational animations, the research methods employed, and the aims and findings of the studies. The second part of this paper will present animated videos produced by teachers together with their experiences from the development process and classroom use. This study concentrates on the software tools the educators chose to use and their perceptions about developing their own animations. Findings indicate that when animated videos are produced by teachers, their creativity is boosted, and their communication skills are enhanced.